Answer:
f(- 6) = 9
Step-by-step explanation:
to evaluate f(- 6), substitute x = - 6 into f(x)
f(- 6) = - × - 6 + 5
= - + 5 = 4 + 5 = 9
A c tv yo TV tctuyrx urxfixufxitcufxgi gixifcit
Option C: is the product of the rational expression.
Explanation:
The given rational expression is
We need to determine the product of the rational expression.
<u>Product of the rational expression:</u>
Let us multiply the rational expression to determine the product of the rational expression.
Thus, we have;
Let us use the identity in the above expression.
Thus, we get;
Simplifying the terms, we get;
Thus, the product of the rational expression is
Hence, Option C is the correct answer.
Number 12 what do you think we do first
Answer:-44
Step-by-step explanation:
-16-(28)=-44